Moodle as an ODL teaching tool: A perspective of students and academics - Zainuddin N.; Idrus R.; Jamal A.F.M. (Academic Publishing Ltd, 2024)
This article describes the use of Moodle as a suitable platform to support the postgraduate open and distance learning (ODL) courses offered by Universiti Sains Islam Malaysia (USIM). Many USIM postgraduate students who take obligatory courses (e.g., research methodology and data analysis) are taught at different venues to facilitate students access to higher education and enhance quality of lifelong learning. Managing this complex teaching network has called for the adaptation of Moodle platform. This approach meets two relevant requirements, (a) to ensure consistency, compliance, and quality of teaching, (b) to reduce educational costs, which largely depend on the number of peripheral venues for teaching activities. This article analyses the functionalities of the Moodle platform and its use among USIM postgraduate students and academics. The data was collected based on content analysis via questionnaire applied to 18 USIM ODL postgraduate students and 4 lecturers. The results show that despite having great potential, Moodle is mainly used as a repository for materials. Moreover, lecturers recognize the importance of the use of other functionalities of this platform in order to promote the success of the teaching and learning process. ACPIL.